Acute high-fat feeding leads to disruptions in glucose homeostasis and worsens stroke outcome. Issue 6 (June 2019) - Haley, Michael J; Krishnan, Siddharth; Burrows, David; de Hoog, Leon; Thakrar, Jamie; Schiessl, Ingo; Allan, Stuart M; Lawrence, Catherine B
Chronic consumption of diets high in fat leads to obesity and can negatively affect brain function. Rodents made obese by long-term maintenance on a high-fat diet have worse outcome after experimental stroke. High-fat consumption for only three days does not induce obesity but has rapid effects on the brain including memory impairment. However, the effect of brief periods of high-fat feeding or high-fat consumption in the absence of obesity on stroke is unknown. We therefore tested the effect of an acute period of high-fat feeding (three days) in C57B/6 mice on outcome after middle cerebral artery occlusion (MCAo). In contrast to a chronic high-fat diet (7.5 months), an acute high-fat diet had no effect on body weight, adipose tissue, lipid profile or inflammatory markers (in periphery and the brain). Three days of high-fat feeding impaired glucose tolerance, increased plasma glucose and insulin and brain expression of the glucose transporter GLUT-1. Ischaemic damage was increased (48%) in mice fed an acute high-fat diet, and was associated with a further reduction in GLUT-1 in the ischaemic hemisphere. These data demonstrate that only a brief period of high-fat consumption has a negative effect on glucose homeostasis and worsens outcome after ischaemic stroke.